Barron's E-Z statistics - Downing, Douglas (E-Z series., 2009)
Presents charts, graphs, diagrams, line illustrations, and explanations of random variables, probability, distributions, polls and sampling, linear regression, and other statistics topics, with exercises and practice questions to help check understanding of basic concepts.